(untitled) (The Pakistan Development Review, 1991)
Privatization as an instrument for development is rmding significant currency in industrial and developing countries throughout the world. 1YPically, its need arises from the concerns over efficiency with which the state can manage public enterprises (PEs) or large and growing claims of these enterprises on national budgets. In Pakistan its need emanates from both. Barring a few years in the early 1970s, the policy of development through private enterprise remained the mainstay of the Government of Pakistan (GOP) economic policy throughout the four decades of the country’s life. In fact, a policy of privatization i.e., transferring public assets to the private sector control remained an enunciated policy in the 1950s and the 1960s, which was again adopted in the late 1970s. However· it was not until late the 1980s that concerted efforts were mounted to breath life into the moribund programme of privatization. In developing a programme for privatization the question faced by us concern the size of the existing PE sector, its performance, constraints in and prerequisite for privatization. The most important question is can we privatize all PEs, if not, then what productivity enhancing measures can we take for enterprises which cannot be privatized in the immediate future.